Cases of Trichohepatoenteric Syndrome (Syndromic Diarrhea) with Underlying Crohn’s Disease - Е. А. Roslavtseva; Т. E. Borovik; Е. G. Tsimbalova; А. О. Anushenko; А. S. Potapov; М. М. Lokhmatov; I. L. Chashchina; М. D. Bakradze (Вопросы современной педиатрии)
Tricho-hepato-enteric syndrome (syndromic, phenotypic diarrhea, SD/THES) is a rare inborn disease, which affects bowels. It is caused by the mutation of genes SKIV2L or TTC37. Manifestations include intrauterine hypotrophy, severe chronic diarrhea, which starts in infancy, characteristic facial features and hair growth abnormalities, immune disorders. There are data on two patients dealing with tricho-hepato-enteric syndrome with underlying Crohn’s disease. This is the first description of cases of aggravated tricho-hepatoenteric syndrome ever found in Russian medical literature.